Faktor-Faktor yang Mempengaruhi Manajemen Laba pada Perusahaan Sub Sektor Tekstil dan Garmen pada Bursa Efek Indonesia - Umar Akbar; Yuniningsih Yuniningsih (Universitas Batanghari Jambi, 2022)
Earnings management is one of the manager's actions in attaching financial statements that are not based on facts. This research seeks to determine, analyze, and test the impact of managerial ownership, profitability, leverage, and company size on the earnings management. Population in this research is manufacturing company sub sector textile and garment listed in Indonesia Stock Exchange year 2017 until 2020. This research has 22 companies population selection of sample by using purpsive sampling method and there are 11 companies that meet the required sample criteria. The method used in this study is multiple regression. The results of this study indicate that managerial ownership, profitability, leverage have no signifcant effect on earnings management, while company size has a significant negative on earnings management.